Leadership Character in the Social Science Subject Theme “My Hero” of the 4th Grade at State Elementary School Purwomartani Kalasan Sleman Yogyakarta - Asnafiyah Asnafiyah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This study aims to describe the learning of leadership characters in the 4th grade social science subject at state elementary school Purwomartani, Kalasan, Sleman, Yogyakarta. This was done because Indonesia seems to have lost its good leadership character which could become an example for children. This research is qualitative with data collection using observation, interview, and documentation techniques. Data analysis was performed through data reduction, data presentation, verification, and conclusion. The results showed that there are several leaders discussed in the 4th grade textbook of elementary school with the theme